UPAYA PROGRAM PENCEGAHAN KHUSUS DI LEMBAGA BIMBINGAN KHUSUS ANAK (LPKA) TERHADAP KASUS DI BAWAH UMUR - Danur Tri Gonggo; Mitro Subroto (Universitas Muara Bungo, 2021)
The existence of punishment is in accordance with the aim of restoring one's own behavior pattern to achieve a reduction in the number of crimes with a deterrent effect for not intending to commit crimes of a general nature. Implementation in accordance with the philosophy of the purpose of punishing children requires a concrete system of procedures. Based on the perspective of Wirjono Prodjodikoro, the special purpose or special prevention is for people who have committed crimes not to think about wanting to do it again through the applicable child development procedures. Of course, during this pandemic, there is a dynamic in the number of cases of underage theft motivated by various pressing factors. So that the Special Child Development Institution (LKPA) requires special procedures that refer to coaching through special preventive efforts as a theory of the purpose of punishment (Utilitarian Theory). This study aims to identify the procedures applied to fulfill children's rights, especially children's rights when undergoing criminal sanctions for children at the Child Special Guidance Institute (LPKA). The results of the research can be used to reflect on their rights and arrangements during the pandemic and how program efforts are being carried out at the institution. This causes LPKA not to fulfill children's rights properly. So it is hoped that this research can provide recommendations for improvement efforts to various parties who supervise LPKA to improve the fulfillment of student rights while undergoing detention during the Covid-19 pandemic